Relationship between transformational leadership, affective commitment and turnover intention of workers in a multinational company / La relación entre liderazgo transformacional, compromiso afectivo e intención de rotación de los trabajadores en una compañía internacional. Issue 1 (2nd January 2020) - Mañas-Rodríguez, Miguel-Ángel; Díaz-Fúnez, Pedro-Antonio; Llopis-Marín, Juan; Nieto-Escámez, Francisco; Salvador-Ferrer, Carmen
ABSTRACT: Transformational leadership is the key to achieving excellent organizational outcomes. Some authors point out that the existence of a transformational leader reduces the likelihood that their employees leave the company. In addition, the intention of abandonment is also reduced when there is a high affective commitment. In this sense, the goal of our work is to know if there is a link between transformational leadership and turnover intention, and also to analyse if such a relationship is mediated by affective commitment. The study was performed in a sample of 706 employees in a multinational company. The scales used were the transformational leadership questionnaire, the affective engagement questionnaire (ISA) and the turnover intention scale. The results show that there is a statistically significant relationship between transformational leadership and turnover intention. We also found that this relationship is mediated by affective commitment.